Experience of using web-quests in computer science lessons in engineering classes - Kutsina S. A. (Engineering education in the conditions of digitalization of society and economy, 2023)
The author substantiates the relevance of the inclusion of web-quests as one of the modern means of teaching computer science and ICT in the educational practice of engineering classes, which is especially significant in the conditions of digitalization of society. The article presents examples of web-quests used in the study of computer science and ICT in engineering classes, during which students find information by searching the Internet and then use it to solve educational-cognitive tasks.
Keywords: средство обучения; цифровизация; digitalization; обучение информатике; инженерный класс; engineering class; web-квест; учебно-познавательное задание; computer science and ICE training; web-quest; educational-cognitive task; learning tool; обучение ИКТ